Modeling and control of plasma rotation for NSTX using neoclassical toroidal viscosity and neutral beam injection. (19th February 2016) - Goumiri, I.R.; Rowley, C.W.; Sabbagh, S.A.; Gates, D.A.; Gerhardt, S.P.; Boyer, M.D.; Andre, R.; Kolemen, E.; Taira, K.
Abstract: A model-based feedback system is presented to control plasma rotation in a magnetically confined toroidal fusion device, to maintain plasma stability for long-pulse operation. This research uses experimental measurements from the National Spherical Torus Experiment (NSTX) and is aimed at controlling plasma rotation using two different types of actuation: momentum from injected neutral beams and neoclassical toroidal viscosity generated by three-dimensional applied magnetic fields. Based on the data-driven model obtained, a feedback controller is designed, and predictive simulations using the TRANSP plasma transport code show that the controller is able to attain desired plasma rotation profiles given practical constraints on the actuators and the available measurements of rotation.